Forecasting of railway freight volume: Approach of Estonian railway to arise efficiency - Hunt, Ülo (Transport, 2003)
The local railroad was substantially deregulated and prepared for privatization by Estonian government in 90's. Changes in commodity mix, length of haul, shipment size, loading weight, equipment ownership, railroad costs, competition from other modes, and demand for railroad transportation have all played a significant role. This paper introduces the importance of forecasting a railway freight volume using the methodology of international knowledge.First Published Online: 19 Dec 2011